SP3.1.10 The use of predictive severity scoring for lower gastrointestinal bleeding in a tertiary colorectal unit. (9th August 2022) - Yao, Sarina; Balfour, James; Boyle, Connor; Ventham, Nicholas
Abstract: Introduction: Lower GI bleeding (LGIB) has an estimated 1-year prevalence of 10% in the UK, accounting for 3% of emergency surgical referrals. The British Society of Gastroenterology (BSG) recommend risk scoring for LGIB to categorise severity and plan management. Experience in a tertiary colorectal centre suggests this potentially overestimates the severity of bleeding and the requirement for inpatient admission. Method: Data was retrospectively collected for all patients referred from primary care or emergency departments with LGIB from 01/05/20–01/04/21. Demographics and an Oakland score (OS), recommended in BSG guidelines, were collected. OS >8 suggests admission. Outcomes following referral, including admission, discharge, blood transfusion and radiological/surgical intervention, were assessed. Results: 294 patients were assessed. 176 patients (59.9%) were admitted for further management. The median OS for admitted patients was 12 (IQR 9–17). 30 patients (10.2%) required blood transfusion, 3 required radiological/surgical intervention (1%). 118 (40.1%) patients were discharged. The median OS was 10 (IQR 8–12). 80 patients discharged had a score >8, recommending admission; 4 patients required readmission (5.0%), however, none required intervention. 38 patients were discharged with a score ≤8; again, 4 patients (10.5%) required readmission for LGIB, with none requiring intervention. Fisher's exact test showed no statistical significance between OS and readmission (p=0.22). Conclusion: Risk assessment scoring recommended admission for a large cohort of patients safely discharged after initial assessment in our centre. A small number required readmission, however, none suffered significant adverse outcomes. Further investigation should assess whether such scoring systems are too cautious for use in specialist colorectal centres.